Selektivitas Penuntutan Kejahatan Internasional dalam Praktik Peradilan Global: Studi Kasus Penanganan Kejahatan Perang oleh International Criminal Court - Anisah Friti Anjelia; Dwi Putri Lestarika (AHKAM, 2026)
The issue of selectivity in the prosecution of international crimes remains a crucial problem in the global criminal justice system. The establishment of the International Criminal Court (ICC) through the Rome Statute aims to enforce accountability and eliminate impunity for perpetrators of serious international crimes, particularly war crimes, but in its implementation the ICC is often considered not to have applied law enforcement evenly. This study aims to examine the characteristics of selectivity in the prosecution of war crimes by the ICC, the factors that influence it, and its impact on the legitimacy of global justice. This study employed a normative legal method with statutory and case analysis approaches. The results of the study show that selectivity in prosecution is influenced by limitations in jurisdictional authority, the application of the principle of complementarity, the ICC’s dependence on state cooperation, and international political dynamics, especially those related to the role of the United Nations Security Council. These conditions are reflected in the tendency for case handling to focus on certain regions and countries, while similar alleged violations involving countries with major political influence are rarely processed to the prosecution stage. These findings indicate that selectivity in prosecution has implications for declining trust in the ICC and has the potential to weaken the effectiveness of international criminal law enforcement. Thus, this study affirms that the legitimacy of global criminal justice depends greatly on consistency, independence, and equality in the enforcement of international law.